2022
DOI: 10.1038/s41598-022-20287-4
|View full text |Cite
|
Sign up to set email alerts
|

Common variants in GNL3 gene contributed the susceptibility of hand osteoarthritis in Han Chinese population

Abstract: Osteoarthritis (OA) is one of the most popular degenerative joint diseases. The nucleolar GTP binding protein 3 (GNL3) gene encodes guanine nucleotide binding protein-like 3, which is related in cell proliferation, differentiation, and cell cycle regulation. Our study aimed to examine the contribution of GNL3 gene polymorphisms to the risk of hand OA and its related clinical features. A total of 3387 study participants including 1160 patients with hand OA and 2227 controls were recruited in this study. Eleven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In Gee et al, the correlations of two polymorphic loci of the genes SPCS1 (rs6617) and GNL3 (rs11177), which are strongly coupled with rs6976 GLT8D1 , with a significant imbalance of gene expression ( SPCS1 and GNL3 , respectively) in cartilage and other joint tissues such as ligaments, meniscus, adipose tissue, synovial membrane, were shown [ 97 ]. A number of studies have established the association of the rs11177 (G>A) GNL3 with the OA risk in both European and Asian populations [ 1 , 31 , 32 , 99 ], including on the GWAS level ( p ≤ 5 × 10 −8 ) [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Gee et al, the correlations of two polymorphic loci of the genes SPCS1 (rs6617) and GNL3 (rs11177), which are strongly coupled with rs6976 GLT8D1 , with a significant imbalance of gene expression ( SPCS1 and GNL3 , respectively) in cartilage and other joint tissues such as ligaments, meniscus, adipose tissue, synovial membrane, were shown [ 97 ]. A number of studies have established the association of the rs11177 (G>A) GNL3 with the OA risk in both European and Asian populations [ 1 , 31 , 32 , 99 ], including on the GWAS level ( p ≤ 5 × 10 −8 ) [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a common chronic degenerative joint disease [ 1 ], resulting in pathological changes in all joint tissues (cartilage/subchondral bone/ligaments/menisci/articular capsule/synovial membrane) [ 2 ]. More than 500 million people worldwide suffer from this disease; an especially high incidence of OA is observed among people over 65 years of age [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been implicated in multiple bioprocesses, including cell proliferation, differentiation, and cell cycle regulation. [116][117][118] GNL3 belongs to the GTP-binding protein family, containing an MMRHSR1 domain. 119 GNL3 is abundantly expressed in bone marrow mesenchymal stem cells (BM-MSCs) and is closely related to the differentiation of chondrocytes.…”
Section: Ythdf2 and Ythdc2mentioning
confidence: 99%
“…119 GNL3 is abundantly expressed in bone marrow mesenchymal stem cells (BM-MSCs) and is closely related to the differentiation of chondrocytes. [116][117][118] Recently, both human and animal studies found that GNL3 were significantly reduced in knee tissues of OA samples compared with non-OA samples. However, the potential mechanism underlying aberrant GNL3 expression in OA remains unclear.…”
Section: Ythdf2 and Ythdc2mentioning
confidence: 99%
See 1 more Smart Citation